EFFECT OF SHEET THICKNESS AND SOJEAN APPLICATION ON DRY MASS GAIN OF FINE-FIBER COTTON DURING THE COMBING PERIOD (Universal International Scientific Journal, 2026)
This article studies the effects of different plant densities and application of sojeangrowth regulator on plant dry mass accumulation during the squaring phase of long staple cotton usingdrip irrigation and a double row planting scheme in soil-climatic conditions of Surkhandarya region,southern zone of Uzbekistan.
Keywords: Fine-fiber Termez-202 cotton variety; dry mass